Who Wants to Work in a Rural Health Post? The Role of Intrinsic Motivation, Rural Background and Faith-Based Institutions in Ethiopia and Rwanda - Serneels, P.; Montalvo, J. G.; Pettersson, G.; Lievens, T.; Butera, J. D.; Kidanu, A. (2012)
Objective To understand the factors influencing health workers' choice to work in rural areas as a basis for designing policies to redress geographic imbalances in health worker distribution. Methods A cohort survey of 412 nursing and medical students in Rwanda provided unique contingent valuation data. Using these data, we performed a regression analysis to examine the determinants of future health workers' willingness to work in rural areas as measured by rural reservation wages. These data were also combined with those from an identical survey in Ethiopia to enable a two-country analysis. Findings Health workers with higher intrinsic motivation - measured as the importance attached to helping the poor as well as those who had grown up in a rural area and Adventists who had participated in a local bonding scheme were all significantly more willing to work in a rural area. The main result for intrinsic motivation in Rwanda was strikingly similar to the result obtained for Ethiopia and Rwanda combined. Conclusion Intrinsic motivation and rural origin play an important role in health workers' decisions to work in a rural area, in addition to economic incentives, while faith-based institutions can also influence the decision.